Gamification in English Language Learning for Seafarers in Preparation for Marlins Test: Enhancing Motivation and Engagement - Yuliana Fatima Dayana; Laila Puspitasari Anggraini; Capt. Suhartini; Aliya Izet Begovic Yahya (South Sulawesi Education Development (SSED), 2025)
This study explores the impact of gamification on motivation and engagement in English language learning among seafarers preparing for the Marlins test. Employing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted to investigate the effects of gamification. The theoretical framework integrates gamification principles and Self-Determination Theory to examine how game-like elements enhance intrinsic motivation and learning outcomes. Results indicate that gamification fosters engagement by providing clear goals, immediate feedback, and a sense of achievement. The findings suggest practical implications for maritime education in creating autonomous learning environments that sustain motivation and enhance language proficiency.